Organization And Management of Educational Activities in Preschool Educational Organizations - Nizomova Sitora Valijonovna (Zien Journals, 2022)
This article provides information about the work of the organization for the organization and management of educational work in preschool organizations
Keywords: preschool institution; organization; education; work